2011
DOI: 10.4049/jimmunol.1002414
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Epithelial Cell-Derived Prostaglandin E2 Dampens the Reactivity of Dendritic Cells

Abstract: Airway epithelial cells regulate immune reactivity of local dendritic cells (DCs), thus contributing to microenvironment homeostasis. In this study, we set out to identify factors that mediate this regulatory interaction. We show that tracheal epithelial cells secrete soluble factors that downregulate TNF-α and IL-12p40 secretion by bone marrow-derived DCs but upregulate IL-10 and arginase-1. Size exclusion chromatography identified small secreted molecules having high modulatory activity on DCs. We observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 55 publications
7
65
1
1
Order By: Relevance
“…In addition, IL-13 expression was not detected in the DC from the tumor-bearing mice (data not shown), indicating that these type-2 cytokines, with the exception of IL-6, are not involved in arginase-1 expression in this model. Moreover, previous studies (46,47) demonstrated that PGE 2 and IL-8 induced arginase expression in mouse DC or human tumor cells. We examined mRNA expression levels of Cox-2, Ptges (PGE 2 -related factors), and KC (murine IL-8 homolog) in the tumor cells used in the present experiments.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, IL-13 expression was not detected in the DC from the tumor-bearing mice (data not shown), indicating that these type-2 cytokines, with the exception of IL-6, are not involved in arginase-1 expression in this model. Moreover, previous studies (46,47) demonstrated that PGE 2 and IL-8 induced arginase expression in mouse DC or human tumor cells. We examined mRNA expression levels of Cox-2, Ptges (PGE 2 -related factors), and KC (murine IL-8 homolog) in the tumor cells used in the present experiments.…”
Section: Discussionmentioning
confidence: 90%
“…PGE2 produced by airway epithelial cells induces the differentiation of DCs with an anti-inflammatory phenotype characterized by reduced secretion of TNF-alpha and increased secretion of IL-10. 97 Airway epithelial cell-derived PGE2 reduces the pro-inflammatory activity of DCs and limits their activity through an EP4 receptor-dependent mechanism. PGE2 has well-established protective and beneficial effects in asthma.…”
Section: Tumor Pathologymentioning
confidence: 99%
“…Isolation and culture of murine tracheal epithelial cells (mTrECs) were performed as previously described (2). Briefly, 8-10-wk-old female C57BL/6 mice (Charles River Laboratories, Sulzfeld, Germany) were sacrificed by CO 2 asphyxia, and tracheae were dissected and digested with Pronase E and DNAseI overnight at 4˚C.…”
Section: Preparation Of Primary Airway Epithelial Cellsmentioning
confidence: 99%
“…Recently, we and others (2,11,12) demonstrated that respiratory epithelial cells are able to suppress proinflammatory cytokine secretion of LPS-stimulated DCs through the constitutive production of PGE 2 , TSLP, macrophage-derived chemokine, or thymus-and activation-regulated chemokine. Other soluble, epithelial cell-derived factors with immune-modulatory potential have been described (1,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation